Per- and polyfluoroalkyl substances and blood lipid levels in pre-diabetic adults—longitudinal analysis of the diabetes prevention program outcomes study. (August 2019) - Lin, Pi-I D.; Cardenas, Andres; Hauser, Russ; Gold, Diane R.; Kleinman, Ken P.; Hivert, Marie-France; Fleisch, Abby F.; Calafat, Antonia M.; Webster, Thomas F.; Horton, Edward S.; Oken, Emily
Abstract: Exposure to per - and polyfluoroalkyl substances (PFASs) may interfere with lipid regulation. However, most previous studies were cross-sectional with the risk of reverse causation, suggesting a need for long-term prospective studies. We examined the relationship of baseline plasma PFAS concentrations with repeated measures of blood lipids. We included 888 prediabetic adults from the Diabetes Prevention Program (DPP) and DPP Outcomes Study, who had measurements of 6 plasma PFAS concentrations at baseline (1996–1999) and repeated measures of blood lipids over 15 years of follow-up, and were initially randomized to placebo or a lifestyle intervention. We used linear regression to examine cross-sectional associations of PFAS concentrations and lipid levels at baseline, and evaluated prospective risks of hypercholesterolemia and hypertriglyceridemia using Cox proportional hazard models, and tested for effect modification by study arm. Participants (65.9% female, 57.0% White, 65.9% aged 40–59 years) had comparable PFAS concentrations [ e.g., median (IQR) perfluorooctanoic acid (PFOA) 4.9 ng/mL (3.2)] with the general U.S. population in 1999–2000. We observed higher total cholesterol at baseline per doubling of PFOA (β: 6.1 mg/dL, 95% CI: 3.1, 9.04), perfluorohexane sulfonic acid (PFHxS, β: 2.2 mg/dL, 95% CI: 0.2, 4.3), and perfluorononanoic acid (PFNA, β: 2.9 mg/dL, 95% CI: 0.7, 5.0). Prospectively, baseline concentrations of several PFASs, including PFOA, PFOS, PFHxS and PFNA, predicted higher risks of incident hypercholesterolemia and hypertriglyceridemia, but only in the placebo group and not the lifestyle intervention group. For example, participants in the placebo group with PFOA concentration > median (4.9 ng/mL) were almost twice as likely (HR: 1.90, 95% CI: 1.25, 2.88) to develop hypertriglyceridemia compared to those ≤median. Findings suggest adverse effects of some PFASs on lipid profiles in prediabetic adults. However, the detrimental effect was attenuated with a lifestyle intervention. Highlights: PFAS may disrupt lipid regulation. We examined PFAS-lipid relationship in prediabetic adults over 15 years. Plasma PFAS concentrations had positive cross-sectional associations with total cholesterol level. Risk of dyslipidemia was elevated in relation to baseline PFAS levels. Lifestyle behaviors may attenuate the adverse effect on lipid profile.